The role of multifunctional agriculture in sustainable tourism development in the area of Stara Planina - Popović, Vesna; Nikolić, Marija; Katić, Branko (Economics of Agriculture, 2010)
The area of Nature Park and tourist region "Stara planina" owes the exceptional natural and cultural values on which base current strategic directions of economic development – tourism and agriculture. A signifcant ecological sensitivity and demographic and structural limitations of the area, emphasizes an importance of these activities sustainable development, which ensures their mutual support in realizing an integral regional development. The sustainable tourism presumes the development of complementary activities – agriculture, handicrafts and services, by promoting a consumption of local products and services and encouraging the employment of local population in tourism. The sustainable agriculture has multifunctional character and relies on the traditional production methods. The production of high nutrition value food, along with providing services of public interest and developing additional activities, ensures the environment protection and long-term sustainable management with natural resources and contributes to tourism development, employment growth, social cohesion and preservation of tradition and cultural heritage.